2021
DOI: 10.1080/14756366.2021.1978081
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of benzamide-hydroxypyridinone hybrids as potent multi-targeting agents for the treatment of Alzheimer's disease

Abstract: A novel class of benzamide-hydroxypyridinone (HPO) derivatives were innovatively designed, synthesised, and biologically evaluated as potential multitargeting candidates for the treatment of Alzheimer's disease (AD) through pharmacophores-merged approaches based on lead compounds 18d , benzyloxy phenyl analogs, and deferiprone (DFP). These hybrids possessed potent Monoamine oxidase B (MAO-B) inhibition as well as excellent iron chelation, with pFe 3+ values ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The orally available iron chelator deferiprone (DFP, 4 ) has been employed in clinical studies to determine its impact on PD progression (Figure 7). 88,89 In a multicenter, unblinded, single‐arm pilot phase II clinical trial ( n = 20, NCT00907283), it was demonstrated that DFP reduced iron accumulation in the globus pallidus in two patients and improved motor symptoms in three patients 90 . Separately, in two randomized, double‐blind, placebo‐controlled phase II clinical trials, DFP reduced iron deposition in SN and progression of dyskinesia in early‐onset PD patients ( n = 19, NCT00943748; n = 22, NCT01539837) 91,92 .…”
Section: Ferroptosis‐related Therapeutic Targets For Pdmentioning
confidence: 99%
“…The orally available iron chelator deferiprone (DFP, 4 ) has been employed in clinical studies to determine its impact on PD progression (Figure 7). 88,89 In a multicenter, unblinded, single‐arm pilot phase II clinical trial ( n = 20, NCT00907283), it was demonstrated that DFP reduced iron accumulation in the globus pallidus in two patients and improved motor symptoms in three patients 90 . Separately, in two randomized, double‐blind, placebo‐controlled phase II clinical trials, DFP reduced iron deposition in SN and progression of dyskinesia in early‐onset PD patients ( n = 19, NCT00943748; n = 22, NCT01539837) 91,92 .…”
Section: Ferroptosis‐related Therapeutic Targets For Pdmentioning
confidence: 99%
“…Several pieces of evidence reported by our research group have revealed that coumarin/benzamide-based multi-target ligands with the iron-chelating ability and MAO-B inhibitory activity have an attractive anti-AD potential 20 , 22 . Aiming at identifying new multipotent ligands, in this work, a new series of chromone-hydroxypyridinone hybrids were rationally designed by linking chromone core and hydroxypyridinone moiety with the appropriate linkers ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 98%
“…It plays an important role in neural plasticity, synapse formation, antimicrobial activity, and iron export. APPs are mainly cleaved by two enzymes: (i) BACE1 and (ii) γ‐secretase, leads to the production of various Aβ‐peptides of different lengths (Aβ 1–40 , and Aβ 1–42 ; Jiang et al., 2021). The longest one is Aβ 1–42 , and the shortest one is Aβ 1–40 .…”
Section: Introductionmentioning
confidence: 99%